Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Pada Medium Gambut Dengan Berbagai Periode Penggenangan - , Nurbaiti; Yulia, Arnis En; Sitorus, Jujung (Jurnal Agro Teknologi Tropika, 2012)
The research has conducted at the green house of Faculty of Agriculture, Riau University from September 2011 toDecember 2011, to study the growth response of palm oil seedling on peat soil with different flooding periods. Theexperimental units were arranged in Completely Randomized Design (CRD) with three treatment flooding periods and sixreplications. Three flooding periods were: no flooding, 5 days of flooding period and 10 days of flooding period. The datawere analyzed by ANOVA and Duncanâs New Multiple Range Test. (DNMRT) at level 5%. The result showed that theperiodical flooding inhibited the enhancement of plant height, leaves number, stem diameter, primary roots number, rootvolume and dry weight palm oil seedlings but enhanced shoot the root ratio. Palm oil seedling could survive by periodicalflooding condition by forming adventitious roots. The number of adventitious roots in the 10 days flooding period weresignificantly different from these the 5 days flooding.